2023
DOI: 10.1177/0958305x231155495
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relationship between resource endowment, financial agglomeration, innovation-driven, and green total factor productivity

Abstract: As conflicts between emissions reductions and economic growth intensify, an increasing number of countries and regions are focusing on green total factor productivity (GTFP). Financial agglomeration (QWS), resource endowment (SE), and innovation-driven (ID) are the main factors that cause regional differences in GTFP. However, few scholars have comprehensively considered the impact of the interaction between SE, ID, and QWS on GTFP. This article uses the Global Malmquist-Luenberger (GML) index to calculate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Columns (1) and ( 2) show the estimation results before and after adding control variables. Column (1) shows that the ecological civilization pilot policies positively affected green technology innovation at the 1% significance level with a regression coefficient of 0.355. Column (2) shows that the regression coefficient of the ecological civilization pilot policies decreases from 0.355 to 0.279 after the inclusion of control variables, but still exerts a positive influence at the 5% significance level.…”
Section: Benchmark Model Regression Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Columns (1) and ( 2) show the estimation results before and after adding control variables. Column (1) shows that the ecological civilization pilot policies positively affected green technology innovation at the 1% significance level with a regression coefficient of 0.355. Column (2) shows that the regression coefficient of the ecological civilization pilot policies decreases from 0.355 to 0.279 after the inclusion of control variables, but still exerts a positive influence at the 5% significance level.…”
Section: Benchmark Model Regression Resultsmentioning
confidence: 99%
“…UR it is the urbanization level, and the meaning of the rest of the variables is the same as Equation (1). Under the premise of proving that the pilot policy has a significant effect on green technology innovation, it is verified in turn whether the pilot policy of ecological civilization has a significant effect on urbanization and urbanization on green technology innovation, and if both are significant, then it means that urbanization played a mediating role in the main effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local governments are in an important position to implement localized intermediary strategies for the global agenda [1]. With the increasing contradiction between emission reduction and economic growth [2,3], the carbon emission situation remains gloomy. In 2022, global energy-related CO2 emissions increased by 0.9%.…”
Section: Introductionmentioning
confidence: 99%
“…At the macro level, Cai et al [14] used the DEA method to measure GTFP in the coal industry using the Global Malmquist-Luenberger productivity index and analyzed the differences in GTFP at the regional level. Li et al [15] further explored the driving factors of GTFP and showed that resource abundance constrained regional GTFP growth and that environmental regulation, investment in science and technology, and human capital have positive effects on GTFP. Also, Fang et al [16] used the SBM-DEA method to measure the GTFP of extractive industries in China.…”
Section: Introductionmentioning
confidence: 99%